FORECASTING THE TEMPERATURE GRADIENT OF COTTON REVOLT - ORIPOV, JASURBEK; Kuldashov, Golibjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In the context of today’s rapidly developing global economy, which is strongly driven by technological production, the issue of ensuring sustainability and safety in agricultural industries has become particularly relevant. Among the most strategically important industries in the Republic of Uzbekistan, cotton production stands out due to its scale and significant contribution to the national economy. However, one of the most serious challenges in this sector is the risk of spontaneous heating and ignition of cotton storage modules, which can result in substantial economic losses, deterioration of fiber quality, and even large-scale fire hazards. This paper explores scientific and engineering approaches aimed at preventing the ignition of cotton storage formations through accurate forecasting and structural modifications.